Causes of pulmonary bleeding in cancer patients - Roman S. Kiselev; Evgeniy A. Tarabrin; Z. G. Berikkhanov; S. Yu. Muravev; M. Yu. Ivanova (Clinical Medicine (Russian Journal), 2026)
Objective. To analyze the causes of pulmonary hemorrhage (PH) in cancer patients. Material and methods. During the period 2010–2022, pulmonary hemorrhage was treated in cancer patients. The causes of PH were analyzed based on the nosology of cancer diseases. The involvement of the great circle of circulation (GCC) was determined based on the presence of direct or indirect radiological signs of bronchial angiography, the clinical outcome of endovascular treatment for PH, and the results of autopsy. CT of the chest with contrast was performed in case of recurrence of LC after bronchial artery embolization (BAE). The source of LC from the vessels of the pulmonary circulation (PC) was determined in case of ineffectiveness of BAE, data of CT of the chest with contrast and results of autopsy. Also, the article discusses the effect of tumor disintegration on the source of LC and complication of FTB with tumor biopsy for the purpose of verification of the process. Results. Squamous cell carcinoma of the lung was the dominant cancer in oncological patients with pulmonary hemorrhage and accounted for 54.3%. The source of LC in oncological diseases in 94.3% was the vessels of the BCC, in 5.7% the vessels of the MCC. A distinctive feature of patients with decay ≥ 50 mm were the ECOG 4 cancer status 57.1% (p = 0.008571) and high hospital mortality 61.9% (p = 0.008571). The recurrence of LC after bronchoscopy with biopsy in these patients was 13.1%. Conclusions. Oncological patients with LC have various nosological forms with their own characteristics. In order to provide adequate and timely treatment for such a serious complication, it is necessary to know exactly which vessels are involved. The presence of a cavity of decay is a prognostic unfavorable factor for the course of the underlying disease. Performing a biopsy in patients with LC in the presence of an unverified cancerous disease carries the risk of recurrent bleeding.